KISS: Jewishness, hard rock and the Holocaust. (1st September 2020) - Stratton, Jon
KISS was a hard rock group, one of the most successful during the second half of the 1970s and early 1980s. The group's two founding members, Gene Simmons and Paul Stanley, were both Jewish. Indeed, both were the sons of Holocaust survivors. This article examines the impact of Simmons's and Stanley's Jewishness on KISS as a rock group and on its success. One of the most obvious impacts was the drive to succeed which Simmons and Stanley shared. Simmons writes about wanting power, Stanley that he wanted respect. As children of survivors they wanted safety. During much of the 1970s, the Holocaust was not yet publicly acknowledged. However, its trauma is evident in, for example, the stage characters that Simmons and Stanley adopted. First, and most obviously, the disguise which hid their Jewishness but, at the same time, Simmons's creation of the Demon and Stanley's Starchild both in different ways acting out their inherited Holocaust trauma. This article addresses the many ways that Simmons's and Stanley's Jewishness, as filtered through the inherited trauma of the Holocaust, impacted on the image and music of KISS.